Investigation of the Stroop Task Effect Using an Orthographic Variation of the 3/\/9[vertical bar]$[vertical bar]-[vertical bar] 14/\/9(_)493 (English Language) - Graham, Kaetlyn; Schiel, Michael (My University, 2012)
Stroop (1932) originally contemplated the effects that two cognitive dimensions have on each other when presented as a compound stimulus. An exploratory pilot study indicated that the Stroop interference was reproduced by Leet words. Additionally, there was a significant change in times from the baseline of reading Leet speak (BRL) to the resulting baseline (RRL). The purpose of this study was to replicate these results, and propose that between the two baseline conditions, a perceptual learning experience occurs.
Color poster with text, graphs, and tables.
Keywords: Video games; Stroop Color and Word Test; Cognition and literacy; English language--Orthography and spelling; Posters